Strategi Pemasaran Dalam Mempertahankan Citra Merek Dan Perilaku Konsumen Terhadap Pembelian Produk PT.Semen Indonesia (Persero) Tbk. - Aulia Life Rahma Putri; Maharani Ikaningtyas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Indonesia's cement industry plays a pivotal role in economic and infrastructural development. PT Semen Indonesia (Persero) Tbk stands out as a leading company in this sector, boasting renowned brands like Semen Gresik, Semen Padang, and Semen Tonasa, producing various types of cement, including Pozzolan Portland Cement (PPC) and Ordinary Portland Cement (OPC). Competing with other major cement players like PT Indocement Tunggal Prakarsa Tbk and PT Holcim Indonesia Tbk, PT Semen Indonesia remains a significant force.This study aims to formulate marketing strategies focusing on maintaining the company's longstanding positive image and influencing consumer behavior towards purchasing its products. Key aspects explored include product quality, pricing, corporate image, customer service, innovation, sustainability, promotion, and socio-cultural factors. Understanding consumer behavior is vital, considering their interest in cement products with a strong brand image, factoring in aspects such as quality, pricing, corporate image, customer service, innovation, sustainability, promotion, and socio-cultural elements. Research findings are expected to provide in-depth insights into PT Semen Indonesia's ability to comprehend and respond to consumer preferences effectively. This understanding will serve as a foundation for formulating smarter and more relevant marketing strategies, aiding the company in maintaining and increasing market share, while reinforcing its image as a leading provider of building solutions in Indonesia. in Indonesia.